Filozofia ekspercka – nieakademicka kontrofensywa filozofii? - Rogacz, Dawid (Człowiek i Społeczeństwo, 2015)
This article is the first Polish presentation of the project of expert philosophy, perceived as a non-academic response to the contemporary crisis of humanities. In the field of metaphilosophy and methodology, expert philosophy tries to cooperate fruitfully with science and market, coming across fundamental research of economy and management studies. Refering to the Sophistic movement, it wants to return to the practical dimension of logic and philosophical ethics. Its crucial issue is how to describe expert knowledge, what is reflected in the didactics.